Technical note: A new laboratory approach to extract soil water for stable isotope analysis from large soil samples - J. Kocum; J. Kocum; J. Haidl; O. Gebousky; K. Falatkova; V. Sipek; M. Sanda; N. Orlowski; L. Vlcek (Hydrology and Earth System Sciences)
A correct soil water extraction represents an initial step in stable water isotope analysis. With this aim, we present a new soil water extraction method based on the principle of complete evaporation and condensation of the soil water in a closed circuit. The proposed device has four extraction slots and can be used up to two times a day. Owing to its simple design, there is no need for any chemicals, gases, or high-pressure or high-temperature regimes. The experimental tests proved that the extraction itself does not cause any major isotope fractionation effects leading to erroneous results. Extraction of pure-water samples shifts the isotope composition by 0.04 ± 0.06 ‰ and 0.06 ± 0.35 ‰ for δ18O and δ2H, respectively. Soil water extraction tests were conducted for five distinct soil types (loamy sand, sandy loam, sandy clay, silt loam, and clay) using 40–150 g of pre-oven-dried soil, which was subsequently rehydrated to 10 % and 20 % water content. The shift in the isotopic composition of these tests ranged between −0.04 ‰ and 0.07 ‰ for δ18O and 0.4 ‰ and 1.3 ‰ for δ2H, with the standard deviations of ± (0.08–0.25) ‰ and ± (0.34–0.58) ‰ for δ18O and δ2H, respectively. The results exhibit high accuracy, which makes this method suitable for high-precision studies where unambiguous determination of the water origin is required.